Live Brugia malayi microfilariae inhibit transendothelial migration of neutrophils and monocytes. - Jan-Hendrik Schroeder; Bigboy H Simbi; Louise Ford; Sara R Cole; Mark J Taylor; Charlotte Lawson; Rachel A Lawrence (PLoS Neglected Tropical Diseases)
Lymphatic filariasis is a major tropical disease caused by the parasite Brugia malayi. Microfilariae (Mf) circulate in the peripheral blood for 2-3 hours in synchronisation with maximal feeding of the mosquito vector. When absent from the peripheral blood, Mf sequester in the capillaries of the lungs. Mf are therefore in close contact with vascular endothelial cells (EC) and may induce EC immune function and/or wound repair mechanisms such as angiogenesis. In this study, Mf were co-cultured with human umbilical vein EC (HUVEC) or human lung microvascular EC (HLMVEC) and the transendothelial migration of leukocyte subsets was analysed. In addition, the protein and/or mRNA expression of chemokine, cytokine and angiogenic mediators in endothelial cells in the presence of live microfilariae were measured by a combination of cDNA arrays, protein arrays, ELISA and fluorescence antibody tests.Surprisingly, our findings indicate that Mf presence partially blocked transendothelial migration of monocytes and neutrophils, but not lymphocytes. However, Mf exposure did not result in altered vascular EC expression of key mediators of the tethering stage of extravasation, such as ICAM-1, VCAM-1 and various chemokines. To further analyse the immunological function of vascular EC in the presence of Mf, we measured the mRNA and/or protein expression of a number of pro-inflammatory mediators. We found that expression levels of the mediators tested were predominantly unaltered upon B. malayi Mf exposure. In addition, a comparison of angiogenic mediators induced by intact Mf and Wolbachia-depleted Mf revealed that even intact Mf induce the expression of remarkably few angiogenic mediators in vascular EC. Our study suggests that live microfilariae are remarkably inert in their induction and/or activation of vascular cells in their immediate local environment. Overall, this work presents important insights into the immunological function of the vascular endothelium during an infection with B. malayi.